Commitment to Sustainability: How Sustainability is Reflected in UAE Universities: An Exploratory Study - Gorpe, T Serra; Masamreh, Anas (Universitas Diponegoro, 2023)
Vision, mission, and value statements are important elements in every organization in communicating the core values and practices the organization follows. In higher education institutions, they play an important role in the road map of the institution and how the institution is engaged with all its stakeholders. The aim of the research is to examine the visibility of information about sustainability on the websites of UAE universities. Universities are important players when it comes to communicating Sustainable Development Goals (SDGs), as they have an important role in societal awareness about sustainable development. To what extent do the mission, vision, and value statements reflect the sustainability of the higher educational institutions that are investigated? The study employs a quantitative content analysis method to explore elements of SDGs by looking for keywords that are associated with the terms ‘sustainable’ or ‘sustainability’ and associated with the 17 SDGs. The sample includes 27 local universities across the UAE. The collected data from universities’ websites are analyzed using AntConc, a software for textual analysis. Only nine universities included a general term for sustainability in their documents. There was a mention of only six SDGs, and SDG9, followed by SDG4, were the most mentioned ones. The performance of the higher educational institutions in sustainability and how these are communicated should be focused strategically. The study will show the way to look at local practices when it comes to SDG communication and be the catalyst for comparative studies that can help establish best practices and guidelines for universities in the region.